Factors influencing delay in presentation and their impact on cancer stage in women with a diagnosis of breast cancer in South Africa - Rayne, Sarah Louise (My University, 2018)
Background Breast cancer is the most common cancer in women in most low- and middle-income countries, and often presents at an advanced stage affecting prognosis irrespective of the care available. Studies from sub-Saharan Africa concerning patients with breast cancer are often presented as a homogeneous group with lack of education, awareness and access commonly cited as reasons for late stage and delay to presentation. Study Rationale This study was designed to explore this uniform characterisation of patients with breast cancer in three parts: first define the relationship of their demographic and socio-economic characteristics with their attitudes, fears and beliefs held regarding breast cancer and its treatment; then determine the relationship of socio-economic and psychosocial characteristics with a patient’s stage at presentation, and delay to presentation; and finally investigate and understand the heterogeneity of breast cancer molecular biology in this population, and assess its independent contribution to late-stage disease. Methods A questionnaire was designed for distribution to breast cancer patients. It included questions about their characteristics, socio-economic circumstances, education, and ability to access care as well as their agreement to statements of knowledge and beliefs about breast cancer. In a pilot study, the questionnaire was distributed to 263 breast cancer patients at two sites (one government and one private health care facility) in Johannesburg. Using a modified questionnaire including time to access care, patients attending the urban government open-access breast unit over a 14-month period with a new diagnosis of breast cancer were then recruited. The stage at presentation and molecular subtype for participants was recorded. The relationship of clinical stage and delay to presentation to demographic variables, beliefs and molecular subtypes were assessed through univariate and multivariate modified Poisson’s regression methods of calculating odds ratio with 95% confidence intervals. Results The pilot study found that fears related to treatments were far stronger than those related to socio-economic barriers, and higher in young women under 40 years. Access to information was protective from adverse beliefs about cancer but positive expressions of cure and beating cancer were found equally in all women. Socio-economic status was a strong confounder of race and explained most of the racial differences in levels of fear. In the final study, 252 women diagnosed with a new breast cancer completed the survey (response rate of 70.8%). Stage 3 (56.0%) was most common at presentation and nearly one third of all patients presented with T4 cancer. Total delay to present at the breast clinic was associated with locally advanced stage at presentation (p=0.021) and most delay occurred between acknowledging a breast symptom and seeking care. Self-reported transport difficulties predicted both advanced stage at presentation and delay to presentation of more than six months. Invasive ductal carcinoma was most common (92.7%), and the most common subtype was Luminal B (57.9%) followed by Luminal A (21.5%), triple negative (13.9%) and HER2 positive (6.7%). HER2 overexpression remained an independent risk factor for late stage at presentation. Conclusions Participant’s beliefs about their new breast cancer diagnosis and breast cancer in general were most commonly appropriate, and showed a low level of fatalism, in contrast to other studies in sub-Saharan Africa. Few beliefs or socio-economic factors influenced delay to presentation or stage at presentation, however this study found that tumour biology has a compelling place in understanding the aetiology of late-stage disease. This thesis has contributed information to the complex interplay that exists between the patient, her environment and the breast tumour biology. It helps us address the issues of access to care, in both patients-related and treatment availability.
A thesis submitted to the Faculty of Health Sciences, University of Witwatersrand, in fulfilment of the requirements for the degree of Doctor of Philosophy Johannesburg 2018